Hospitalizations and deaths due to pertussis in children from 1996 to 2013 - Janayne F. Mançaneira; Juliana R. Benedetti; Linjie Zhang (Jornal de Pediatria, 2016)
Objectives: To assess temporal trends of hospitalizations and deaths from pertussis in Brazilian children in the period of 1996–2013. Methods: This was a descriptive ecological study of temporal trends, based on the DATASUS database. The number of hospitalizations and deaths from pertussis in children up to 19 years of age from January 1996 to December 2013 was obtained. Descriptive statistics were applied for data analysis. Results: During the study period, a total of 19,047 hospital admissions from pertussis were recorded, of which 88.2% occurred in infants younger than 1 year. In the period 1996–2010, the mean annual number of admissions was 755, ranging from a maximum of 1179 in 2004 to a minimum of 400 in 2010. There was an increase of admissions in the last three consecutive years (2011, 2012, and 2013) with 1177, 2954 and 3589 hospitalizations, respectively. There were 498 deaths from pertussis throughout the study period, of which 96.8% occurred in children younger than one year. There was an increase in the number of deaths from pertussis in children in the years 2011, 2012, and 2013, with 40, 93, and 87 recorded deaths, respectively. The increase in hospitalizations and deaths from pertussis in children occurred in all regions of the country, with the highest increase observed in the Southeast, North and Northeast regions. Conclusions: There was a substantial increase in hospitalizations and deaths from pertussis in children for three consecutive years (2011, 2012, and 2013) in all Brazilian regions. The most affected age group was that of children younger than one year. Resumo: Objetivos: Avaliar tendência temporal de internações e óbitos por coqueluche em crianças brasileiras no período de 1996 a 2013. Métodos: Trata-se de um estudo ecológico descritivo de tendência temporal, baseado no banco de dados DATASUS. Foram extraídos os números de internações e de óbitos por coqueluche em crianças até 19 anos de idade no período de janeiros de 1996 a dezembro de 2013. A estatística descritiva foi aplicada para análise de dados. Resultados: No período estudado foram registradas 19.047 internações por coqueluche, das quais 88,2% foram lactentes menores de um ano. No período de 1996 a 2010, o número médio anual de internações foi de 755, oscilando entre o máximo de 1179 em 2004 e o mínimo de 400 em 2010. Houve um acréscimo de internações nos últimos três anos consecutivos (2011, 2012 e 2013), com 1177, 2954 e 3589 registros, respectivamente. Ocorreram 498 óbitos por coqueluche em todo o período estudado, dos quais 96,8% eram menores de um ano. Houve acréscimo no número de óbitos por coqueluche em crianças nos anos 2011, 2012 e 2013, com 40, 93 e 87 registrados, respectivamente. O aumento de internações e óbitos por coqueluche em crianças ocorreu em todas as regiões do país, havendo maior acréscimo nas regiões Sudeste e Norte-Nordeste. Conclusões: Houve um aumento substancial de internações e de óbitos por coqueluche em crianças por três anos consecutivos (2011, 2012 e 2013) em todas as regiões brasileiras. A faixa etária mais atingida foi a de menores de um ano. Keywords: Pertussis, Hospitalization, Death, Ecological study, Palavras-chave: Coqueluche, Internação, Óbito, Estudo ecológico